Biological responses of human solid tumor cells to X‐ray irradiation within a 1.5‐Tesla magnetic field generated by a magnetic resonance imaging–linear accelerator. Issue 7 (19th July 2016) - Wang, Li; Hoogcarspel, Stan Jelle; Wen, Zhifei; van Vulpen, Marco; Molkentine, David P.; Kok, Jan; Lin, Steven H.; Broekhuizen, Roel; Ang, Kie‐Kian; Bovenschen, Niels; Raaymakers, Bas W.; Frank, Steven J.
Abstract : Devices that combine magnetic resonance imaging with linear accelerators (MRL) represent a novel tool for MR‐guided radiotherapy. However, whether magnetic fields (MFs) generated by these devices affect the radiosensitivity of tumors is unknown. We investigated the influence of a 1.5‐T MF on cell viability and radioresponse of human solid tumors. Human head/neck cancer and lung cancer cells were exposed to single or fractionated 6‐MV X‐ray radiation; effects of the MF on cell viability were determined by cell plating efficiency and on radioresponsiveness by clonogenic cell survival. Doses needed to reduce the fraction of surviving cells to 37% of the initial value (D0s) were calculated for multiple exposures to MF and radiation. Results were analyzed using Student's t‐ tests. Cell viability was no different after single or multiple exposures to MRL than after exposure to a conventional linear accelerator (Linac, without MR‐generated MF) in 12 of 15 experiments (all P > 0.05). Single or multiple exposures to MF had no influence on cell radioresponse (all P > 0.05). Cells treated up to four times with an MRL or a Linac further showed no changes in D0s with MF versus without MF (all P > 0.05). In conclusion, MF within the MRL does not seem to affect in vitro tumor radioresponsiveness as compared with a conventional Linac. Bioelectromagnetics. 37:471–480, 2016. © 2016 Wiley Periodicals, Inc.